2014
DOI: 10.5219/365
|View full text |Cite
|
Sign up to set email alerts
|

Sensory quality, colour and oxidative stability of cured cooked ham with propolis extract

Abstract: The effect of 0.06% propolis ethanol extract on the sensory quality, colour and oxidative stability of cured cooked ham was evaluated. Half of the experimentally processed hams treated with 0.06% ethanolic extract of propolis with ascorbic acid (EEP), only with ascorbic acid (AA) and control samples (C) were sliced and vacuum packaged. Samples were kept at 4 °C 21 days (sliced) respectively 20, 50 and 100 days (unsliced). The results revealed that all samples were characterized without any significant colour d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 16 publications
0
10
0
1
Order By: Relevance
“…A study performed by Kročko et al (2014) using the propolis extract associated with ascorbic acid in the sliced baked ham demonstrated that the use of propolis did not interfere in the product acceptance. Bernardi et al (2013) evaluated the acceptance of salami with propolis with 50 habitual consumers of salami.…”
Section: Sensory Acceptance and Purchase Intentionmentioning
confidence: 99%
“…A study performed by Kročko et al (2014) using the propolis extract associated with ascorbic acid in the sliced baked ham demonstrated that the use of propolis did not interfere in the product acceptance. Bernardi et al (2013) evaluated the acceptance of salami with propolis with 50 habitual consumers of salami.…”
Section: Sensory Acceptance and Purchase Intentionmentioning
confidence: 99%
“…This remarkable combination makes it an excellent candidate for preserving different foods. Successful experiments have been performed for utilization of propolis extracts in the preservation of numerous products: fruit juices [62][63][64][65], fruits [68][69][70][71][72][73][74][75][76][77], vegetables [78][79][80][81][82][83][84][85], eggs [86][87][88][89][90][91], meat and fish products [92][93][94][95][96][97][98][99][100] (Table 2). This field of application of propolis is rapidly growing, as indicated by the growing number of publications.…”
Section: New Fields Of Propolis Applicationmentioning
confidence: 99%
“…Hawaiiana) Ethanol extract Llanta Azul apiary, Zaragoza (Antioquia -Colombia) [77] Vegetables Rice (Oryza sativa, var. hinohikari) Absolute ethanol, methylene chloride and hexane extracts Brazilian green propolis [78] Carrot (minimally processed) 25% Water and alcohol extracts Brazilian green propolis [79] Lettuce Ethanol extract Bragança, Portugal [80] Cucumber 70% Ethanol extracts Pato Branco (PR), Brazil [81] Beans, carrots against white rot disease Alcohol extract Iraq [82] Mixed vegetables for soup Propolis extract Argentina [83] Celery, leek and butternut squash (minimally processed) Ethanolic extract; standardized to 10% propolis extract Mendoza province, Argentina [84] Chilli (Capsicum annuum L.) Ethanol extract Brazilian green propolis [85] Eggs Eggs quality during storage 70% Ethanol extract Hatay province, Turkey [86,87] Japanese quail eggs 70% Ethanol extract Hatay province, Turkey [88][89][90] Hens eggs Ethanol extract Parana state, Brazil, [91] Meat products Fresh oriental sausage 95% Ethanol extract Cairo, Egypt [92] Sausages 96% Ethanol extract Boyacá, Colombia [93] Fermented meat sausage "Alheira" 95 % ethanol Vila Franca, Viana do Castelo, Portugal [94] Beef patties Commercial ethanol extracts Sonora, Mexico, poplar type [95] Poultry meat product-cured cooked ham 96% Ethanol extract Slovakia [96] Fish products Nile tilapia (Oreochromis niloticus) fillets, frozen storage Water extract Egypt [97] Cachama fish (Piaractus brachypomus) fillets (refrigeration) 96% Ethanol extract Boyacá, Colombia [98] Fresh fish burgers 70% Ethanol extract La California, LI, Italy [99] Fresh shibuta (Barbus grypus) fillets Water extract Fanus Natural Company, Trabzon, Turkey [100] Others Milk protein concentrate (diary beverages) 94 % Ethanol extract Water extract Canada [101] Food packaging Chitosan-propolis coated polypropylene films 80% Ethanol extract Konya region, Turkey. [102] Antimicrobial edible coating of Bell Pepper 95% Ethanol extract China [103] Active film with antimicrobial effect, reduces oxidation of butter during storage 70% Ethanol extract Brazilian red propolis …”
Section: 3mentioning
confidence: 99%
“…Additionally, it has been proposed as an ingredient to increase the shelf life of fruits, vegetable oils, and meat and dairy products [17,18]. Its use as an antioxidant in meat products allowed the reduction of lipid oxidation [19], avoiding the reduction of sensory quality of products associated with changes in color, texture, and appearance of rancid odor and flavor, which influences consumer acceptance [20], as well as a decrease in the nutritional value due to the loss of essential fatty acids and vitamins [4]. In this way, a preliminary study carried out by our research group showed that propolis extract (PE, 2%) incorporation in bovine and porcine patties significantly reduced (p < 0.05) Lox and Pox, as well as color loss, thereby increasing the oxidative stability of patties during refrigerated storage [21].…”
Section: Introductionmentioning
confidence: 99%